Identifying competency gaps in intra- and post-learning of a pediatric residency program: a qualitative study - Putra, David Anggara; Sekarhandini, Pitra; Moelyo, Annang Giri (Paediatrica Indonesiana, 2024)
Background The purpose of the pediatric residency program is for aspiring pediatricians to develop the core competencies needed to care for the children’s health. Upon graduation, pediatricians encounter competency challenges related to diverse populations, cultures, and medical facilities across the nation. Enhancing the efficacy and efficiency of medical education in pediatric residency programs requires identifying and addressing gaps in the post-learning outcomes and intra-learning processes. Objective To investigate competency gaps between the core competencies taught in the pediatric residency training program and the actual necessitates in the professional experience of pediatricians. Methods This qualitative study was conducted by a focus group discussion using semi-constructed questions. Twelve pediatricians who graduated from the Pediatric Residency Program of Universitas Sebelas Maret and had professional work experience of 3 to 18 months were included. Focus group discussions were held online and moderated by the research team using guided questions. Two FGD sessions of 5 and 7 subjects each were conducted. The discussions were recorded and transcribed for analysis in a stepwise manner involving data grouping, information labeling, and data coding to identify the main themes. Results All subjects were working in type B, C, and D hospitals in six different provinces at the time of the study. The competency gaps in intra-residency learning domain covered two topics: curriculum content (core competencies, medicolegal education, effective communication, vaccination, and longitudinal case management) and training (case variations, patient complexity, and affiliated hospital rotations). The smallest competency gaps was core competency; and there was a need for improvement in other topics, particularly in effective communication and vaccination. The competency gaps in the post-learning domain included 4 topics: daily practices (demographic differences, popular topics, and effective communication), health facilities (the gap between individual competency and availability of health facilities), professional relationships with senior/other center colleagues, and strategic plans (continuing medical education). The cultural social background of the population and limited health resources were the main issues in the post-learning are-sxa that need be acknowledged. Effective communication was the theme that emerged and should be to be taught in both ares of learning and post-learning. Conclusion Pediatric residency graduates should address some gaps in learning after completing the pediatric residency program. Effective communication was identified as a learning gap during and after training. Based on our findings, we recommend for the program to provide additional steps to prepare pediatric residents before their graduation.